JURNAL KESEHATAN EFEKTIFITAS TERAPI SUPLEMEN ZAT BESI (IRON POLYMALTOSE COMPLEX) TERHADAP KENAIKAN KADAR HB PADA PASIEN ANEMIA - Maryanti S.SiT.,M.Kes (STIKES DUTAGAMA KLATEN, 2022)
Anemia is a public health problem that often occurs, especially in developing countries (WHO, 2015). Iron deficiency anemia has an impact on iron deficiency in children with a prevalence of 43% at the age of 6-59 months and 25% in children aged 5-15 years, which combined represents 600 million cases of anemia, of which half are iron deficient. The purpose of this study was to determine the hemoglobin level in respondents before being given therapy and hemoglobin levels in respondents after being given IPC therapy, as well as to determine the effectiveness of giving IPC to increase hemoglobin. The research is included in analytical research with experimental quai design. The population in this study were pediatric patients who had anemia and were given IPC therapy for 3 months regularly, as many as 150 respondents during the last 3 months. With a purposive sampling technique with a sample of 51 respondents who fit the inclusion and exclusion criteria. The therapy given is IPC therapy for 3 months regularly. Analysis of the data used is the T test, with 0.05. The results showed that the T count was 3.15677 > T Table 1.67591, which means that Ho is rejected and Ha is accepted, meaning that IPC therapy is effective in increasing hemoglobin levels in children.